A Comparative Study of the Role of Local Newspapers in Rural Development in Three Selected Blocks in West Bengal - Ujjwal Ganguly; Shahnaaz Zabi (International Journal of Rural and Regional Development, 2025)
This study aims to investigate and compare the role of local newspapers in facilitating rural development with a focus on three selected blocks in North 24 Parganas district in West Bengal, India. Local newspapers are a significant communication medium in rural areas, influencing community awareness, mobilization, and development initiatives. The study employed a mixed-methods approach, combining qualitative interviews, content analysis of newspapers, and surveys to comprehensively understand the impact challenges faced by local newspapers in contributing to rural development. The findings underscore the role of the newspaper in disseminating information, promoting local culture, and acting as a platform for community engagement. This study aims to explore the role of local newspapers in rural development, focusing specifically on three selected blocks in the North 24 Parganas district of West Bengal. By comparing these blocks, the study seeks to assess how effectively local newspapers disseminate information on rural development and influence knowledge, attitudes, and actions among rural communities. By examining the role of local newspapers in rural development, this study seeks to contribute to the broader understanding of how communication influences development outcomes. It will provide insights into the effectiveness of local newspapers as a medium for disseminating information about government schemes, engaging rural communities, and promoting public participation in development programs.
Keywords: Rural Development; community engagement; local culture; local newspaper